Point-of-care blood tests during home visits by out-of-hours primary care clinicians; a mixed methods evaluation of a service improvement - Hayward, G; Dixon, S; Garland, S; Glogowska, M; Hunt, H; Lasserson, D (BMJ Publishing Group, 2020)
Objectives We aimed to evaluate test usage and patient and clinician experience following the introduction of point-of-care (POC) blood tests into a primary care out-of-hours service.